Description of two new species of Cenophengus (Coleoptera: Phengodidae: Cenophenginae), with an assessment of their phylogenetic position in the genus - Vega-Badillo, Viridiana; Roza, André Silva (Zootaxa, 2025)
Cenophengus is one of the most species-rich genera within the family Phengodidae, with 30 species distributed from south USA to Costa Rica. This study describes two new species of Cenophengus, C. fagerstromi sp. nov. from Honduras and C. zaragozai sp. nov. from Mexico. Detailed morphological descriptions, including diagnostic characters, are provided for each of the new species, in addition to an updated key for species of the genus. In addition, the phylogeny of Cenophengus is reanalyzed by incorporating the newly described species into the existing data set. This updated phylogenetic analysis offers a more complete understanding of the evolutionary relationships within the genus.